2018
DOI: 10.1101/272450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

pathfindR: An R Package for Pathway Enrichment Analysis Utilizing Active Subnetworks

Abstract: PathfindR is a tool for pathway enrichment analysis utilizing active subnetworks. It identifies gene sets that form active subnetworks in a protein-protein interaction network using a list of genes provided by the user. It then performs pathway enrichment analyses on the identified gene sets. Further, using the R package pathview, it maps the user data on the enriched pathways and renders pathway diagrams with the mapped genes. Because many of the enriched pathways are usually biologically related, pathfindR a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Gene ontology enrichment analysis performed on pathfindR (v. 1.2.1) [69] showed that GPR161 (upregulated) was associated with the negative regulation of the hedgehog signaling pathway. However, previous studies revealed that abnormal activation of this pathway is related to cell proliferation in endometrial cancer [70,71].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene ontology enrichment analysis performed on pathfindR (v. 1.2.1) [69] showed that GPR161 (upregulated) was associated with the negative regulation of the hedgehog signaling pathway. However, previous studies revealed that abnormal activation of this pathway is related to cell proliferation in endometrial cancer [70,71].…”
Section: Resultsmentioning
confidence: 99%
“…KEGG analysis also performed on pathfindR (v. 1.2.1) [69] indicated that the upregulated genes HDAC7, GTF2A1L, and MAPKAPK2 were involved in the viral carcinogenesis pathway. Previous studies have demonstrated that inhibition of histone deacetylases, such as HDAC7, induces apoptosis, cell cycle arrest, and growth inhibition in endometrial cancer cells [76][77][78][79].…”
Section: Resultsmentioning
confidence: 99%
“…We obtained the frequently mutated cancer driver genes from the COSMIC [40] database. Using these cancer driver DE genes, we identified enriched biological pathways listed in REACTOME via a pathway enrichment tool Pathfinder [41]. Similarly, we identified cancer driver DE genes for each cell line and computed cell line-specific enriched REACTOME based pathways.…”
Section: Computing Sample and Cell Line-specific Biological Pathwaysmentioning
confidence: 99%
“…Countless tools for pathway analysis exist. Some of the widely used pathway analysis tools are GSEA [114], DAVID [115], IPA [116], SPIA [117], pathfindR [118], enrichr [119], reactomePA [120], MetaCore [121], and PathVisio [122]. Additionally, many different pathway resources exist, the most popular of which are Kyoto Encyclopedia of Genes and Genomes [123], Reactome [124], WikiPathways [125], MSigDb [126], STRINGDB [127], Pathway Commons [128], Ingenuity Knowledge Base [129], and Pathway Studio [130].…”
Section: Clinical Interpretation Of Genomic Variationsmentioning
confidence: 99%